Design of high frequency integrated analogue filters - Sun, Yichuang (Institution of Engineering and Technology, 2002)
The book covers the following areas: high frequency integrated analogue filter; operational transconductance amplifier; gm-C filter; MOSFET-C technique; active filter; integrated inductor; log domain filter; low voltage technique; switched-current filter; analogue adaptive filter; and on-chip automatic tuning.